Pengembangan Media Pembelajan Buletin Berorientasi HOTS (Higher Order Thinking Skill) Pada Materi Laju Reaksi Di SMA Negeri 1 Kelam Permai - Meisya Tri Farida; Tuti Kurniati; Fitriani Fitriani (Jurnal Ilmiah Ar-Razi, 2020)
This study aims to produce a media which is bulletin with HOTS (Higher Order Thinking Skill) oriented and verify the validity and feasibility of the result. The method used in this research is Research and Development (R&D) using ADDIE design which is carried out through 5 stages, (1) Analysis, (2) Design, (3) Development, (4) Implementation, (5) Evaluation. Research subject 30 student of XI MIPA 1 in SMA Negeri 1 Kelam Permai. Data collection techniques used were media validation questionnaire and student response questionnaire. The validity of media bulletin was rated by 4 validator, 2 media experts and 2 material experts. The validation of development media bulletin obtained an average value of validity 1,00 with high criteria. The percentage of the result of student response questionnaire in small group trial is 86,25% with very practical criteria. The percentage of  the result of student response questionnaire in field test is 76,91% with practical criteria. Based on the result of research, it is known that, the developed HOTS oriented bulletin is very suitable to be used in teaching Laju reaksi.